Quality practices in supply chain system reduces cost of quality : a study of the oil and gas industry - Maruthamuthu, Amuthamalar (2017)
This management project provides an insight on how quality practices such as ISO 9000, TQM and 6 Sigma functions within an intricate supply chain system in the oil and gas industry. This management project was carried out on three Subsea Production System projects in an operating oil and gas company within Asia Pacific region. Based on empirical data analysis and findings on cost of quality occurrence on these three projects, this research provides meaningful results in showing how quality practises implemented within a supply chain system reduces cost of quality incurred by the operating company.